Behavioral tests predicting striatal dopamine level in a rat hemi-Parkinson's disease model. (January 2019) - Miyanishi, Kazuya; Choudhury, Mohammed E.; Watanabe, Minori; Kubo, Madoka; Nomoto, Masahiro; Yano, Hajime; Tanaka, Junya
Abstract: Parkinson's disease (PD) is a frequent neurodegenerative disease causing bradykinesia, tremor, muscle rigidity and postural instability. Although its main pathology is progressive dopaminergic (DArgic) neuron loss in the substantia nigra, motor deficits are thought not to become apparent until most DArgic neurons are lost, probably due to compensatory mechanisms that overcome the decline of DA level in the striatum. Even in animal PD models, it is difficult to detect motor deficits when most DArgic neurons are functional. In this study, we performed various behavioral tests (apomorphine-induced rotation, cylinder, forepaw adjustment steps (FAS), beam walking, rota-rod, and open-field), using 6-hydroxydopamine (OHDA) and lipopolysaccharide (LPS)-induced hemi-PD model rats with various striatal DA levels, to find the best way to predict the DA level from earlier disease stages. Different from the 6-OHDA-induced model, reduction in the striatal DA levels in the LPS-model was less significant. Among the behavioral tests, data from cylinder and FAS tests, which evaluate forelimb movements, best correlated with decline of the DA level. They also correlated well with decreased body weight gain. The beam and apomorphine tests showed less significant correlation than the cylinder and FAS tests. Open-field and rota-rod tests were not useful. Expressional levels of mRNA encoding tyrosine hydroxylase (TH), a marker of DArgic neurons, correlated well with the DA level. Metabotropic glutamate receptor 4 mRNA expression correlated with the striatal DA level and may be related to compensatory mechanisms. These results suggest that motor impairments of PD should be evaluated by forelimb movements, or hands and forearms in clinical settings, rather than movement of the body or large joints. The combination of cylinder and FAS tests may be the best to evaluate the rat PD models, in which many DArgic neurons survive. Graphical abstract: Highlights: The 6-OHDA- and LPS-induced Parkinson's disease (PD) rat models were used. Cylinder and FAS tests are suitable to evaluate motor deficits of forelimbs. Forelimb impairments correlated linearly with striatal dopamine (DA) decline. Apomorphine-induced rotation was apparent when DArgic neurons were totally lost. For early detection of PD, examination of hand and forearm movements is suitable.